1997
DOI: 10.1084/jem.185.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Response Modifier A (CrmA) Inhibits Ceramide Formation in Response to Tumor Necrosis Factor (TNF)-α: CrmA and Bcl-2 Target Distinct Components in the Apoptotic Pathway

Abstract: Proteases are now firmly established as major regulators of the “execution” phase of apoptosis. Here, we examine the role of proteases and their relationship to ceramide, a proposed mediator of apoptosis, in the tumor necrosis factor-α (TNF-α)–induced pathway of cell death. Ceramide induced activation of prICE, the protease that cleaves the death substrate poly(ADP-ribose) polymerase. Bcl-2 inhibited ceramide-induced death, but not ceramide generation. In contrast, Cytokine response modifier A (CrmA), a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
135
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 62 publications
(87 reference statements)
16
135
2
Order By: Relevance
“…Treatment of MDA-MB-231 breast cancer cells with 100 µM pamidronate resulted in a time-related increase in DNA fragmentation which reached approximately six-fold compared to control by day 3 of treatment. In addition, substantial induction of DNA fragmentation by this concentration of pamidronate was also identified in two other breast cancer cell lines, Hs 578T and MCF-7, and levels were comparable to those achieved with two known inducers of apoptosis, cell-permeable C2 ceramide and TNF-α (Dbaibo et al, 1997). Direct comparison of the two bisphosphonates pamidronate and zoledronate in inducing DNA fragmentation shows that zoledronate is the more potent bisphosphonate with a substantial increase in fragmented DNA levels, at concentrations as low as 10 µM.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Treatment of MDA-MB-231 breast cancer cells with 100 µM pamidronate resulted in a time-related increase in DNA fragmentation which reached approximately six-fold compared to control by day 3 of treatment. In addition, substantial induction of DNA fragmentation by this concentration of pamidronate was also identified in two other breast cancer cell lines, Hs 578T and MCF-7, and levels were comparable to those achieved with two known inducers of apoptosis, cell-permeable C2 ceramide and TNF-α (Dbaibo et al, 1997). Direct comparison of the two bisphosphonates pamidronate and zoledronate in inducing DNA fragmentation shows that zoledronate is the more potent bisphosphonate with a substantial increase in fragmented DNA levels, at concentrations as low as 10 µM.…”
Section: Discussionsupporting
confidence: 53%
“…Similar increases in the proportion of fragmented DNA were also detected in Hs578T and MCF-7 cells treated for 2 days with 100 µM pamidronate (Table 1). Results are comparable to those obtained with tumour necrosis factor α (TNF-α) (20 ng ml -1 for 2 days) and cell-permeable C2 ceramide (20 µM for 3 days), both of which have been shown to induce apoptosis in breast cancer cells (Dbaibo et al, 1997). To compare the effects of zoledronate with pamidronate on DNA fragmentation, Hs 578T cells were treated with zoledronate or pamidronate (10, 50 and 100 µM) for 3 days.…”
Section: Changes In Nuclear Morphologymentioning
confidence: 61%
“…In contrast, some recent studies have shown that Bcl-2 overexpression did not a ect ceramide accumulation in response to certain anti-cancer drugs Allouche et al, 1997) or receptor agonists (Dbaibo et al, 1997, Wiesner et al, 1997. However, in these individual studies, only a single overexpressing clone was used and there is no precise assessment regarding the expression levels of Bcl-2 or Bcl-xL.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that the inhibition of ceramide accumulation by Bcl-2 overexpression during apoptosis induced by chemotherapeutic agents, irradiation, or hypoxia (Yoshimura et al, 1998;Tepper et al, 1999). In contrast, other studies have demonstrated that overexpression of Bcl-2 or Bcl-xL failed to prevent ceramide formation in response to certain anti-cancer drugs Allouche et al, 1997) or receptor agonists (Dbaibo et al, 1997;Wiesner et al, 1997). At present, therefore, the mechanism underlying the Bcl-2-mediated protection against the ceramide signaling pathway is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Fas-mediated and TNF-a-mediated apoptosis was completely inhibited by expressing the crmA gene, which is markedly different from the antiapoptotic action of Bcl-2. 40 CrmA has also been reported to inhibit perforin/granzyme-Bmediated apoptosis. 22,41 Furthermore, caspase-1 is known to be a key caspase in perforin/granzyme-Bmediated apoptosis, while Acetyl-Asp-Glu-Val-Asp-aldehyde (Ac-YVAD-CHO), a caspase-1-specific inhibitor, blocks perforin/granzyme-B-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%